Gentzen's Centenary The Quest for Consistency - Kahle, Reinhard; Rathjen, Michael (Springer International Publishing : Imprint: Springer, 2015)
Gerhard Gentzen has been described as logic's lost genius, whom Gödel called a better logician than himself. This work comprises articles by leading proof theorists, attesting to Gentzen's enduring legacy to mathematical logic and beyond. The contributions range from philosophical reflections and re-evaluations of Gentzen's original consistency proofs to the most recent developments in proof theory. Gentzen founded modern proof theory. His sequent calculus and natural deduction system beautifully explain the deep symmetries of logic. They underlie modern developments in computer science such as automated theorem proving and type theory. .